1972
DOI: 10.1252/jcej.5.297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Performance of Mixing Apparatus for High Viscosity Fluids

Abstract: There exists no universally accepted technique for evaluating the functional status of equipment for high-viscosity mixing based upon generalized basic information such as flow patterns and shearing deformation characteristics. This paper deals with the measurement of flow patterns. After obtaining the overall flow patterns in a mixing vessel, circulation capacity and fluid deformations which cover information about energy dissipation were correlated with the homogenizing time. The physical meanings of C^nT^an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 1 publication
2
8
0
1
Order By: Relevance
“…A variation in streamline pattern with a change of Reynolds number was ob tained. These patterns agreed qualitatively with the experimental results of Peters andSmith (1967,1969) and Murakami et al (1972), and it was found that the mean rotational velocity of the fluid relative to the impeller was affected slightly by Reynolds number and decreased with increasing Reynolds number.…”
Section: Conclusion and Significancesupporting
confidence: 89%
See 2 more Smart Citations
“…A variation in streamline pattern with a change of Reynolds number was ob tained. These patterns agreed qualitatively with the experimental results of Peters andSmith (1967,1969) and Murakami et al (1972), and it was found that the mean rotational velocity of the fluid relative to the impeller was affected slightly by Reynolds number and decreased with increasing Reynolds number.…”
Section: Conclusion and Significancesupporting
confidence: 89%
“…These patterns show tendencies similar to those of the experimental results reported by Peters andSmith (1967, 1969) and Murakami et al (1972). Namely, with increasing Reynolds number, the symmetry evidence of the flow respect to the blade is gradually lost, and at Re = 50, a region where the fluid moves with the blade is seen behind the blade as shown in Figure 8.…”
Section: Flow Patternssupporting
confidence: 87%
See 1 more Smart Citation
“…Its value is closely related to the way, in which liquid circulates in the tank. As follows from the literature, the main geometrical parameters affecting the circulation in the tank are the diameter and the pitch of the ribbon (Bourne and Butler, 1969;Murakami et al, 1972;Soliman, 1985). With a decrease of clearance c between the rotating ribbon and the tank wall the peripheral and axial velocities in the tank increase, so the rate at which the external part of wall layer is "scratched off" from the wall grows.…”
Section: Introductionmentioning
confidence: 99%
“…Two-blade impellers are generally used for smooth mixing with the tip speed varying from 1.2 to 2.3 m/s. These impellers have been experimentally and theoretically studied previously, Several types of experimental equipment have been used in order to study the flow structure generated by blade impellers (Murakami et al, 1972; Kuriyama et al, 1982; Bertrand and Couderc, 1982;Youcefi, 1993 of these studies show that for a low impeller speed, the flow is essentially tangential. Hiraoka et al (1978) and Bertrand and Couderc (1981) studied the 2D flow of viscous Newtonian and non-Newtonian fluids generated by two-blade impellers and paddle agitators, using Computational Fluid Dynamics.…”
mentioning
confidence: 99%